Analysis of the Study of the Role of Husband's Assistance on Childbirth Anxiety in Primigravida: Observational Study at Sikakap Health Center, Mentawai Islands, Indonesia - Silvia, Elwitri; Ratih Septiana Arpen; Lasmaida Simbolon (HM Publisher, 2024)
Childbirth anxiety is a common phenomenon experienced by primigravidae and can have a negative impact on the birthing process and the health of the mother and baby. Husband's assistance during childbirth has been proven to help reduce childbirth anxiety. This study aims to analyze the role of the husband's assistance on childbirth anxiety in primigravida at the Sikakap Health Center, Mentawai Islands, Indonesia. This research uses an analytical observational design with a cross-sectional approach. Data was collected from 100 primigravidas who gave birth at the Sikakap Health Center, Mentawai Islands, Indonesia. Data were analyzed using the Chi-square test and logistic regression. The results of the study showed that there was a significant relationship between the husband's assistance and childbirth anxiety in primigravida (p<0.001). Primigravidas who were accompanied by their husbands during childbirth had a lower risk of childbirth anxiety compared to primigravidas who were not accompanied by their husbands (OR=0.23, 95% CI: 0.09-0.51). In conclusion, Husband's assistance has been proven to reduce childbirth anxiety in primigravida. Therefore, efforts need to be made to increase husbands' participation in childbirth assistance at the Sikakap Health Center, Mentawai Islands, Indonesia.